Desain Lembar Kerja pada Materi Pemanasan Global Berbasis Argumentasi Toulmin untuk Meningkatkan Kemampuan Pemecahan Masalah (Universitas Negeri Surabaya, 2023)
This research was to find of the validity of worksheets on global warming material based on Toulmin's argumentation to improve problem solving abilities. This research is research using the R&D method with the ADDIE development model. This model uses three stages in research, namely, the analysis stage, namely to find out the types of needs of students regarding global warming worksheets, the design stage, namely designing worksheets to be developed, and the development stage, namely compiling and implementing validation on the developed Toulmin argumentation-based worksheet. The validity of the developed worksheet is assessed from several aspects, namely, the didactic aspect is seen from the use of the worksheet, the constructive aspect is assessed from the use of sentences and the language used in the worksheet, and the technical aspect is seen from the appearance, title, design, etc. . The analysis technique was carried out by calculating the results of the validity of the worksheets from 3 validators namely, 2 expert lecturers and 1 high school teacher. The results of the analysis of the worksheets show that the average value of the three validators in the didactic aspect is 97.5% in the very valid category, in the constructive aspect it is 100% in the very valid category, and in the technical aspect it is 95% in the very valid category. Based on these results the average value of the validity of all aspects obtained a value of 97.5% with a very valid category. So it can be concluded that the worksheet on global warming material based on Toulmin's argumentation to improve problem solving abilities is feasible to use in the learning process. Keywords: Worksheet, Toulmin’s argumentation, Global warming, Problem solving